Zebrafish Genome Engineering Using the CRISPR–Cas9 System. Issue 12 (December 2016) - Li, Mingyu; Zhao, Liyuan; Page-McCaw, Patrick S.; Chen, Wenbiao
Abstract : Geneticists have long sought the ability to manipulate vertebrate genomes by directly altering the information encoded in specific genes. The recently discovered clustered regularly interspaced short palindromic repeats (CRISPR)–Cas9 endonuclease has the ability to bind single loci within vertebrate genomes and generate double-strand breaks (DSBs) at those sites. These DSBs induce an endogenous DSB repair response that results in small insertions or deletions at the targeted site. Alternatively, a template can be supplied, in which case homology-directed repair results in the generation of engineered alleles at the break site. These changes alter the function of the targeted gene facilitating the analysis of gene function. This tool has been widely adopted in the zebrafish model; we discuss the development of this system in the zebrafish and how it can be manipulated to facilitate genome engineering. Trends: Clustered regularly interspaced short palindromic repeats (CRISPR)–Cas9 is an RNA-directed endonuclease that can generate double-strand breaks (DSBs) in the zebrafish genome. CRISPR–Cas9 mutagenesis can be used to make conditional alleles to study tissue-specific or stage-specific gene function. Multigenic mutagenesis using CRISPR–Cas9 can be used to identify and study genetic redundancy and to establish epistatic relationships between genes. CRISPR–Cas9 can be used for whole-genome forward genetic screens. This opens to exploration biological processes that have been genetically intractable. Elucidation of the precise mechanism by which the CRISPR–Cas9 DSB is repaired is likely to expand our ability to perform gene conversion through homology-dependent and homology-independent means.